READING TRANSGENDER AUTOBIOGRAPHIES: EXPLORING IMPLICATIONS OF MALE GAZE ON HIJRA INDIVIDUALS - Maibangsa, Hamsringdi; Jyoti Jayal (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This study examines how autobiographical narratives in the Indian transgender discourse serve as influential tools that enable hijra individuals to offer insights into their lived experiences and complex identities. It focuses on the representation of the “male gaze” in their narratives and its consequent impact on hijra individuals. By analyzing two prominent autobiographies, Me Hijra, Me Laxmi by Laxmi and The Truth About Me: A Hijra Life Story by A. Revathi, this study investigates the manifestation of the “male gaze” on hijra individuals in addition to their experience of marginalization. Employing Norman Fairclough’s model of critical discourse analysis (CDA) alongside the conceptualization of the ‘male gaze’ as an analytical framework, this study analyzes and interprets language that has been used to reveal the societal prejudices and gendered preconceptions.